Antibody‐Mediated Rejection in Lung Transplantation: Clinical Outcomes and Donor‐Specific Antibody Characteristics. Issue 4 (4th February 2016) - Roux, A.; Bendib Le Lan, I.; Holifanjaniaina, S.; Thomas, K. A.; Hamid, A. M.; Picard, C.; Grenet, D.; De Miranda, S.; Douvry, B.; Beaumont‐Azuar, L.; Sage, E.; Devaquet, J.; et al.
Abstract : In the context of lung transplant (LT), because of diagnostic difficulties, antibody‐mediated rejection (AMR) remains a matter of debate. We retrospectively analyzed an LT cohort at Foch Hospital to demonstrate the impact of AMR on LT prognosis. AMR diagnosis requires association of clinical symptoms, donor‐specific antibodies (DSAs), and C4d + staining and/or histological patterns consistent with AMR. Prospective categorization split patients into four groups: (i) DSA positive, AMR positive (DSA pos AMR pos ); (ii) DSA positive, AMR negative (DSA pos AMR neg ); (iii) DSA limited, AMR negative (DSA Lim ; equal to one specificity, with mean fluorescence intensity of 500–1000 once); and (iv) DSA negative, AMR negative (DSA neg ). AMR treatment consisted of a combination of plasmapheresis, intravenous immunoglobulin and rituximab. Among 206 transplanted patients, 10.7% were DSA pos AMR pos (n = 22), 40.3% were DSA pos AMR neg (n = 84), 6% were DSA Lim (n = 13) and 43% were DSA neg (n = 88). Analysis of acute cellular rejection at month 12 showed higher cumulative numbers (mean plus or minus standard deviation) in the DSA pos AMR pos group (2.1 ± 1.7) compared with DSA pos AMR neg (1 ± 1.2), DSA Lim (0.75 ± 1), and DSA neg (0.7 ± 1.23) groups. Multivariate analysis demonstrated AMR as a risk factor for chronic lung allograft dysfunction (hazard ratio [HR] 8.7) and graft loss (HR 7.56) for DSA pos AMR pos patients. Our results show a negative impact of AMR on LT clinical course and advocate for an early active diagnostic approach and evaluation of therapeutic strategies to improve prognosis. Abstract : The authors find an association between antibody‐mediated rejection in lung transplantation and chronic lung allograft dysfunction and graft loss.